1990
DOI: 10.1007/bf01600306
|View full text |Cite
|
Sign up to set email alerts
|

Metastasizing neuroendocrine carcinoma of the larynx with calcitonin and somatostatin secretion and CEA production, resembling medullary thyroid carcinoma

Abstract: A 55-year-old man presented with a metastasizing moderately differentiated neuroendocrine carcinoma of the larynx (atypical carcinoid). Immunocytochemical demonstration of neuroendocrine markers (neuron-specific enolase and chromogranin-A) and presence of membrane-bound neurosecretory granules in the cells established the neuroendocrine nature of the tumour. In addition, the tumour was found to produce calcitonin, somatostatin and carcino-embryonic antigen (CEA). Calcitonin and somatostatin were also secreted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 17 publications
1
24
0
2
Order By: Relevance
“…However, there are rare exceptions as three out of over 300 reported cases of moderately differentiated neuroendocrine carcinoma of the larynx in the literature were reportedly associated with an elevated level of calcitonin. [19][20][21] In each of these three cases, thyroidectomies were performed and the evaluated tissue was reportedly negative for medullary carcinoma. Despite the recognition that only very rare cases of moderately differentiated neuroendocrine carcinoma of the larynx may have elevated serum calcitonin levels, a marker at the light microscopic level would be helpful for objectively distinguishing moderately differentiated neuroendocrine carcinoma of the larynx from medullary carcinoma of the thyroid.…”
Section: Ttf-mentioning
confidence: 99%
“…However, there are rare exceptions as three out of over 300 reported cases of moderately differentiated neuroendocrine carcinoma of the larynx in the literature were reportedly associated with an elevated level of calcitonin. [19][20][21] In each of these three cases, thyroidectomies were performed and the evaluated tissue was reportedly negative for medullary carcinoma. Despite the recognition that only very rare cases of moderately differentiated neuroendocrine carcinoma of the larynx may have elevated serum calcitonin levels, a marker at the light microscopic level would be helpful for objectively distinguishing moderately differentiated neuroendocrine carcinoma of the larynx from medullary carcinoma of the thyroid.…”
Section: Ttf-mentioning
confidence: 99%
“…The literature on NCL is fragmented over numerous case reports and series of small sample size, often with contradicting results, making it difficult to decide on an appropriate treatment strategy. Consequently, physicians facing these tumors often resort to treatment paradigms developed for better known neoplasms (eg, squamous cell carcinoma).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a functional paragan glioma described by Justrabo et al [48], fluorometric assay revealed high norepinephrine and epinephrine lev- 3 Authors refer to the same patient. Neuroendocrine neoplasms of the larynx may release various hormone and enzyme markers into the blood but high serum levels of calcitonin [6,28,48], somatostatin [28] and NSE [28] have rarely been recorded.…”
mentioning
confidence: 99%